Digital HR, Employee Empowerment, Internal Mobility, Career Development on ‎Knowledge Innovation, and Employee Engagement in Technology Firms in Indonesia - Mintawati, Hesri; Maulana , Agung; Pratiwi, Intan Deanida; Sedera, Rakotoarisoa Maminiaina Heritiana; Wen, Goh Khang; Aridan, Muhammad (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to explore the relationships between Digital Human Resource Management, Employee Empowerment, Internal Mobility, Career Development, Knowledge Innovation, and Employee Engagement in Indonesian technology companies. Methodology: A quantitative approach was used, collecting data from 675 employees via a structured questionnaire with a five-point Likert scale. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3.0). Main Findings: Digital HR directly influences Employee Empowerment and Internal Mobility, which positively affect Career Development. Career Development impacts Knowledge Innovation and Employee Engagement, with Knowledge Innovation serving as a mediator between Career Development and Engagement. Novelty/Originality of this study: This study integrates Resource-Based View (RBV) and Social Exchange Theory (SET), demonstrating how Digital HR competencies and employee reciprocity drive innovation and engagement, providing insights for HR managers in technology firms to enhance talent development and competitiveness.